2021
DOI: 10.3390/electronics10060760
|View full text |Cite
|
Sign up to set email alerts
|

High Velocity Lane Keeping Control Method Based on the Non-Smooth Finite-Time Control for Electric Vehicle Driven by Four Wheels Independently

Abstract: In order to improve the output response and robustness of the lane keeping controller for the electric vehicle driven by four wheels independently (EV-DFWI), the article proposes a lane keeping controller based on the non-smooth finite-time (NoS-FT) control method. Firstly, a lane keeping control (LKC) model was built for the EV-DFWI. Secondly, a tracking method and error weight superposition method to track error computing for the lane keeping control based on the LKC model are proposed according to the lane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The simulation results and from the comparison to the slide mode controller technique showed that the proposed technique has a good control result for the active FWS of an electrical vehicle. The article (Meng et al, 2021) recommended a lane-tracking controller using a non-smooth finite-time control technique. A lane-tracking control prototype was built and a tracking scheme and error weight superposition technique to track error computing for the lane-tracking control were suggested by depending on the given information of the used lane line.…”
Section: Finite-time Control: Approaches and Reviewmentioning
confidence: 99%
“…The simulation results and from the comparison to the slide mode controller technique showed that the proposed technique has a good control result for the active FWS of an electrical vehicle. The article (Meng et al, 2021) recommended a lane-tracking controller using a non-smooth finite-time control technique. A lane-tracking control prototype was built and a tracking scheme and error weight superposition technique to track error computing for the lane-tracking control were suggested by depending on the given information of the used lane line.…”
Section: Finite-time Control: Approaches and Reviewmentioning
confidence: 99%
“…Lane detection and following is a fundamental task that can be accomplished with classical methods or can benefit from combining methods based on deep learning and further pre-or post-processing [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Meng et al presented 'High Velocity Lane Keeping Control Method Based on the Non-Smooth Finite-Time Control for Electric Vehicle Driven by Four Wheels Independently' [6], in which two kinds of tracking error computing methods of lane keeping control for electric vehicles were proposed to tackle different conditions, and a Non-FT lane keeping controller was designed to keep the EV-DFWI running in the desired lane suffering external disturbances.…”
mentioning
confidence: 99%